Matrix converter induction motor drive - Altun, H; Sünter, S (Springer-Verlag, 2003)
This paper presents a model in Simulink, which consists of a three-phase matrix converter, an induction motor, a field-oriented controller, and a power supply. A simplified Venturini's modulation algorithm is used in the simulation model. This algorithm provides unity fundamental displacement factor at the input regardless of the load displacement factor and can be easily implemented in closed loop operation. Simulation results are presented for both input and output sides of the converter. These results demonstrate a high-performance matrix converter-fed induction motor drive with unity input displacement factor.
Keywords: matrix converter; induction motor; field-oriented control